Genetics and sports: An overview of the pre-molecular biology era - Peeters, M. W.; Thomis, M. A. I.; Beunen, G. P.; Malina, R. M. (Genetics and Sports, 2009)
Estimated genetic and environmental contributions to individual differences in physical performance phenotypes, responsiveness to intermittent, aerobic and strength training, and specific skill training protocols are the focus of this chapter. Data are derived primarily from twin and family studies, although methods of analysis vary considerably. Estimates of heritability span a wide range for several performance phenotypes and the responsiveness to training. This is explained, in part, by differences in sample characteristics and analytical strategies. Corresponding data for skill acquisition are very limited. Data dealing with the effects of age, sex, maturation and ethnicity on heritability estimates are lacking, and information on behavioral phenotypes that may be related to performance is not available. (Autorreferat)